Dynamic interplay between non-coding enhancer transcription and gene activity in development. - Hamamoto, K.; Umemura, Y.; Makino, S.; Fukaya, T. (Nature communications, 2023)
Non-coding transcription at the intergenic regulatory regions is a prevalent feature of metazoan genomes, but its biological function remains uncertain. Here, we devise a live-imaging system that permits simultaneous visualization of gene activity along with intergenic non-coding transcription at single-cell resolution in Drosophila. Quantitative image analysis reveals that elongation of RNA polymerase II across the internal core region of enhancers leads to suppression of transcriptional bursting from linked genes. Super-resolution imaging and genome-editing analysis further demonstrate that enhancer transcription antagonizes molecular crowding of transcription factors, thereby interrupting the formation of a transcription hub at the gene locus. We also show that a certain class of developmental enhancers are structurally optimized to co-activate gene transcription together with non-coding transcription effectively. We suggest that enhancer function is flexibly tunable through the modulation of hub formation via surrounding non-coding transcription during development.